2019
DOI: 10.1126/scisignal.aay2369
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Notch intracellular domain ankyrin repeat stack by NRARP promotes feedback inhibition of Notch signaling

Abstract: Canonical Notch signaling relies on regulated proteolysis of the receptor Notch to generate a nuclear effector that induces the transcription of Notch-responsive genes. In higher organisms, one Notch-responsive gene that is activated in many different cell types encodes the Notch-regulated ankyrin repeat protein (NRARP), which acts as a negative feedback regulator of Notch responses. Here, we showed that NRARP inhibited the growth of Notch-dependent T cell acute lymphoblastic leukemia (T-ALL) cell lines and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…HEY1 is regulated by MAML1 in melanoma [ 54 ] and human umbilical venous endothelial cells [ 55 ]. NRARP is a negative regulator of Notch signaling [ 56 ] and in Xenopus, the NRARP complex can include Mastermind [ 57 ]. SPP1 is a direct target of the Notch pathway in osteoblasts [ 51 ] and human hepatocellular carcinoma [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEY1 is regulated by MAML1 in melanoma [ 54 ] and human umbilical venous endothelial cells [ 55 ]. NRARP is a negative regulator of Notch signaling [ 56 ] and in Xenopus, the NRARP complex can include Mastermind [ 57 ]. SPP1 is a direct target of the Notch pathway in osteoblasts [ 51 ] and human hepatocellular carcinoma [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed the Notch responsiveness of all genes tested, and also revealed variation in the kinetics of response, even among "canonical" Notch target genes. For example, HES1 showed fast induction followed by rapid down-regulation, consistent with autoinhibition (Hirata et al, 2002), whereas HES4, HES5, and NRARP (a feedback inhibitor of NTC function (Jarrett et al, 2019)) showed more sustained increases in expression ( Figure 2C).…”
Section: Identification Of a Notch-induced Program Of Gene Expressionmentioning
confidence: 75%
“…HIPK2 overexpression was reported in papillomavirus-positive tonsillar squamous cell carcinoma and correlated with the prognosis of patients [22]. HIPK2 regulates malignant growth through the phosphorylation of Notch1 [23]. Many studies also revealed the anti-tumorigenic mechanisms of HIPK2, such as apoptosis stimulation, angiogenesis inhibition, and metastasis prevention [17].…”
Section: Discussionmentioning
confidence: 99%